2003
DOI: 10.1111/j.1524-4725.2003.29394.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pigmented Basal Cell Carcinomas Arising in the Normal-Appearing Skin After Radiotherapy for Carcinoma of the Cervix

Abstract: The latent period for radiation-induced skin cancer is generally very long; secondary skin cancers can develop very late in life. Patients previously treated with radiation therapy require careful follow-up for life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
1
11
0
2
Order By: Relevance
“…In general, there is an increased risk of developing SCC after exposure to high doses of radiation. Low dose radiation exposure is linked to development of BCC, tinea capitus, acne vulgaris, atopic dermatitis, and hyperhydrosis [9]. Our study identified seven cases of BCC and two cases of melanoma in a group of 78 survivors (11.54%) where the mean age was 29.7 years of age.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In general, there is an increased risk of developing SCC after exposure to high doses of radiation. Low dose radiation exposure is linked to development of BCC, tinea capitus, acne vulgaris, atopic dermatitis, and hyperhydrosis [9]. Our study identified seven cases of BCC and two cases of melanoma in a group of 78 survivors (11.54%) where the mean age was 29.7 years of age.…”
Section: Discussionmentioning
confidence: 93%
“…Chronic radiation damage can lead to telangiectasias, irregular hyperpigmentation, skin atrophy, and scar formation [9]. Scarring in the general population ranges from 1.5 to 4.5% compared to 33.3% in the present sample.…”
Section: Discussionmentioning
confidence: 97%
“…[1] These mostly resulted from inappropriate doses of X-rays for treatment of inflammatory dermatoses, being characteristically localized in the field of irradiation. [1,3] The latent period for the development of these cancers is not yet known, but we suspect it to be long and to increase proportionally with time from exposure. Some authors suggest that BCC occurs at low to moderate levels of ionizing radiation, in contrast to SCC, that appears after exposure to high doses of radiation.…”
Section: Discussionmentioning
confidence: 95%
“…En effet, la dose absorbée totale reçue par notre patient lors du traitement de son cancer spinocellulaire avoisinait les 60 Gy ; élément à prendre en considération pour expliquer éventuelle-ment l'incrimination de la radiothérapie externe dans la genèse des deux autres carcinomes. Quant au temps de latence nécessaire pour le développement de cancers cutanés radioinduits, il varie généralement de cinq à 65 ans [61,62]. Arai et al [63] suggèrent, pour retenir le diagnostic de cancer radioinduit, que le délai entre l'irradiation et l'apparition du cancer soit d'au moins deux ans et que celui-ci se développe au sein du champ d'irradiation, comme c'est le cas chez notre patient.…”
Section: Discussionunclassified